Upper mantle temperatures and lithosphere-asthenosphere system beneath the French Massif Central constrained by seismic, gravity, petrologic and thermal observations - Sobolev, Stephan; Zeyen, Hermann; Granet, Michel; Achauer, Ulrich; Bauer, Christian; Werling, Friederike; Altherr, Rainer; Fuchs, Karl (Tectonophysics, 1997)
The new tomographic image of the mantle beneath the French Massif Central reaching a depth of 270 km is interpreted in terms of mantle temperature, considering effects of anharmonicity and anelasticity on seismic velocities as well as effects of mineral reactions, composition and partial melt. For every block of the tomographic model we calculate the absolute temperature required to fit the observed velocity perturbation, the average temperature of the tomographic layer being constrained by P-T estimates from mantle xenoliths and by surface heat flow. From the 3-D temperature distribution we estimate the topography of the thermal lithosphere-asthenosphere boundary as well as 3-D distributions of density, absolute P- and S-velocities and seismic attenuation. The observed velocity perturbations in the mantle beneath the Massif Central can be explained nearly entirely by temperature variations. Temperatures approach the dry peridotite solidus in the depth range from 50 to 90 km just below Cenozoic volcanic areas, but no large-scale partial melting is required to fit the seismic observations. Model temperatures agree well with P-T estimates from mantle xenoliths and measured surface heat flow. Model-predicted seismic velocities, seismic attenuation and density fit well the observations from seismic refractions, surface waves and gravity. The model predicts a broad uplift of the thermal lithosphere-asthenosphere boundary to a depth of 65-70 km with a 50-70 km wide band of stronger lithospheric thinning which crosses the main volcanic fields and strikes parallel to the direction of maximal compression in the crust. The Limagne Graben, which is the major rift structure of the Massif Central, has no clear expression in the topography of the lithosphere-asthenosphere boundary. Our interpretation suggests a mantle plume below the central and southern part of the Massif Central with a potential temperature which is about 150-200°C higher than the average potential temperature of the upper mantle. The structure of the lithosphere-asthenosphere boundary provides evidence for a possible thinning of the mantle part of the lithosphere beneath the volcanic fields parallel to the direction of minimal horizontal compression in the crust.